Hegemoni “Agama Resmi” Dan Ambiguitas Kebebasan Berkeyakinan Penghayat Sapta Darma Di Jember, Jawa Timur - Widianto, Ahmad Arif; Hasanah, Fitriatul (Jurnal SMART (Studi Masyarakat, Religi, dan Tradisi), 2024)
Violations of freedom of religion or belief continue to pose significant challenges to interfaith cooperation. Adherents of indigenous beliefs frequently experience such violations despite the legal and formal guarantees of their religious rights. Believers, as a minority group, are often marginalized and subjected to restrictions, even though their identity is recognized by Constitutional Court Decision Number 97/PUU-XIV/2016. This article examines the hegemonic relationship between "official religion" and adherents of indigenous belief, as well as its impact on the freedom of belief in Sukoreno Village, Jember. The study looks into the practice of hegemony and its implications on the violations of freedom of belief experienced by Sapta Darma Believers. The originality of this research lies in its focus on hegemonic relations through socio-cultural mechanisms. A qualitative methodology is implemented to investigate the disparities in social relations from the standpoint of Sapta Darma believers. Data collection is conducted through semi-structured interviews, supplemented by direct observation to contextualize and comprehend the social practices of interfaith life. The exercise of hegemony include: 1) internalization of Islamic practices within the Sapta Darma community, 2) restriction on certain activities, as well as 3) oversight and regulation concerning permits for the believers. Findings indicate hegemony in the interactions between Muslims and Sapta Darma believers through socio-cultural mechanisms. Although social relations between Muslims and the adherents appear harmonious and peaceful, the potential for violations of religious freedom persists due to the dynamics of majority-minority relations. The believers are compelled to adhere to detrimental policies to sustain harmony and preserve the image of Sukoreno 'Pancasila' Village. The hegemony of the dominant official religion over Sapta Darma belivers engenders ambiguity concerning religious freedom.